KEWENANGAN NOTARIS SEBAGAI PEJABAT LELANG KELAS II BERDASARKAN PERATURAN MENTERI KEUANGAN NOMOR 93/PMK.06/2010 TENTANG PETUNJUK PELAKSANAAN LELANG - Amir Hakim Hasyim (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : A Notary is a Public Official which is authorized to make authentic deeds by the Notary Occupation Act.A Notary can double as a Land Deed Officer (PPAT) which is authorized to make authentic deeds regarding certain legal actions on the land right. The PPAT’s authority is to make the Transfer of Right deed, the Imposition of Right deed such as the Power of Attorney’s Mortgage Right Imposing (SKMHT), and the imposition of Mortgage Right Deed (APHT) in a Credit Agreement between a Debtor and creditors (in this case Banks or Non-Bank Financing Institutions). A Notary can also double as a Second Class Auction Officer (hereinafter referred to as a Notary PL-2) all at once making a minutes of auction deed as it is stipulated in UUJN Article 15 Paragraph (2) Point g. First class auction officer is a special position which is given by the Ministry of Finance cq. Directorate General of State Finance cq. Service Office of State Property and Auction. An Auction or a Public Sales is an open to public sales of goods at a increased or a decreased written and/or oral price quote in order to achieve the highest price and was preceded by the auction’s announcement. The First Class and Second class Auction Officer’s authority is regulated in the Finance Minister’s Regulation (PMK) Number 93/PMK.06/2010 regarding the Implementation Guideline for auction, where there are three classifications on auction, which are the execution auction, the mandatory non-execution auction and the voluntary non-execution auction. Within the mandatory execution auction there is the Execution auction Article 6 of the Mortgage Right Law (UUHT) classification. However, the UUHT auction authority should only be held by a First Class Auction officer from the Ministry of Finance. Notary PL-2 is not given the authority over the UUHT execution auction, eventhough the notary as the PPAT also gave the birth of the Mortgage right on the mortgage right burdened land right certificate and issued the mortgage right certificate (SHT). Certificate are the two formal requirements that ougth to be met by creditors in the implementation petition of the Article 6 UUHT execution auction. Keywords: second class auction Officer, Auction, Notary